2022
DOI: 10.3389/fcvm.2022.900313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Prognosis of Hereditary Transthyretin Amyloid Cardiomyopathy: A Single-Center Study in South China

Abstract: BackgroundHereditary transthyretin amyloid cardiomyopathy (ATTR-CM) is a genotypically heterogeneous disorder with a poor prognosis. There is limited literature describing the variants responsible for ATTRv in areas outside the United State, the United Kingdom and Europe. This study was performed to describe the clinical characteristics and genotypic profiles of this disease in South China.MethodsThis was a single-center retrospective study that evaluated 29 patients with a confirmed diagnosis of hereditary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…In addition to CTS, it is consistently more prevalent among patients with ATTRwt with cardiac involvement; for patients with ATTRv the prevalence is more variable, depending on the mutation. While no cases of CTS were recorded in patients with the Val30Met mutation (a variant without cardiac involvement), [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] it was described in the 19.7% of those with the Ile68Leu mutation. 34 With reference to the prognostic implication of CTS, Milandri et al 34 showed that CTS might be an independent risk factor for mortality in patients with ATTR, especially when secondary to deposits of the ATTRwt form (HR 3.36, 95% CI 1.27-10.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CTS, it is consistently more prevalent among patients with ATTRwt with cardiac involvement; for patients with ATTRv the prevalence is more variable, depending on the mutation. While no cases of CTS were recorded in patients with the Val30Met mutation (a variant without cardiac involvement), [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] it was described in the 19.7% of those with the Ile68Leu mutation. 34 With reference to the prognostic implication of CTS, Milandri et al 34 showed that CTS might be an independent risk factor for mortality in patients with ATTR, especially when secondary to deposits of the ATTRwt form (HR 3.36, 95% CI 1.27-10.3).…”
Section: Discussionmentioning
confidence: 99%
“…26 In terms of SS, the lumbar spinal canal stenosis is the correlated with ATTR-CM. Several studies only looked for SS in the lumbar section, 20,25,30,31 some others did not specify where the stenosis was located 24,27,33 and just Nakagawa et al 17 studied all the spinal sections. They observed four patients with SS in their series, two of them had lumbar spinal canal stenosis, and the other two had cervical spinal canal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…ATTR-CA can be classified into two types: hereditary/mutant (ATTRm) and wild type (ATTRwt) [2] . A total of 120 transthyretin gene mutations have been reported up to date [3] . In China, the most common ATTR mutation is Ala117Ser (previously Ala97Ser) substitution [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 120 transthyretin gene mutations have been reported up to date [3] . In China, the most common ATTR mutation is Ala117Ser (previously Ala97Ser) substitution [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Sensorimotor polyneuropathy, autonomic dysfunction, and gastrointestinal disturbances are the main clinical manifestations of the disorder, which may lead to death after 7.3 years of the disease onset (Conceição and De Carvalho, 2007 ; Koike et al, 2012 ). For ATTRv-CM, amyloidogenic fibers can infiltrate all cardiovascular structures, including the conduction system, atrial and ventricular myocardium, valvular tissue, and coronary and aortic arteries (Wang et al, 2022 ), with myocardial infiltration leading to a progressive increase in the thickness of the right and left ventricular walls, ultimately leading to heart failure (Buxbaum et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%